A 5-year evaluation of early-and late-onset sporadic colorectal cancer screening in central Saudi Arabia - Georgios Zacharakis; Abdulaziz Almasoud; Omar Arahmaner; Khaled Aldossary; Jamaan Alzahrani; Sameer Al-Ghamdi; Abdullah AlShehri; Pavlos Nikolaidis; Abdullah Bawazir; Talal Alfayez; Moataz Daadour; Faisal Alslimah; et al. (The Saudi Journal of Gastroenterology, 2023)
Background: The Al-Kharj colorectal cancer (CRC) screening program was implemented for five years (2017-2022) in a central urban area of Riyadh Province, Saudi Arabia, to assess the participation and impact of the program in average-risk individuals. Methods: The high sensitivity-guaiac based-fecal occult blood test (HSgFOBT) was used as a first-line investigation to identify asymptomatic patients, aged 45–75 years, requiring CRC screening using colonoscopy. The program was run in three tertiary hospitals in the area. Results: The five-year participation rate was 73% (35,640/48,897). The average age was 53 years (range 45–75), 49% were female (17,464/35,640), all were asymptomatic, and 77% had adequate bowel preparation. The HSgFOBT (+) rate was 6.3% (n = 2245), and 76% (n = 1701) of these underwent colonoscopy. The prevalence of findings were as follows: CRC, 4.8% (81/1701); advanced adenoma, 9.5% (162/1701); adenoma, 15.9% (270/1701); non-adenomatous polyps, 7.9% (135/1701); and no polyps or tumors, 25.4% (432/1701). Among participants aged 45–50 years, early onset-CRC had female predominance, while those ≥50 years with late onset-CRC were predominantly male. CRC was more prevalent in the left colon (P < 0.005). Conclusions: Approximately one-third of the participants diagnosed with CRC had early-onset CRC. Screening participation was desirable for the defined target population. Public education is necessary along with expanded colonoscopy resources to continue further citizen participation.